2001
DOI: 10.1007/s005860100249
|View full text |Cite
|
Sign up to set email alerts
|

Corrective surgery for idiopathic scoliosis after heart transplantation

Abstract: Cardiac transplant surgery is being performed with increasing frequency as a treatment for end-stage heart disease. In addition to the well-known post-surgical problems of rejection and infection, these patients may present at a future date with other medical problems which require surgical treatment, including orthopaedic pathology. Severe idiopathic scoliosis has been described in association with congenital heart disease, and its surgical treatment poses considerable risks because of heart disease. Spinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In children with organ transplants these risks are even higher. The patients need their daily immunosuppressive medication also perioperatively [11,14], which may result in delayed wound healing and increased risk of postoperative infections [9]. In our series, these problems, however, were not observed.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In children with organ transplants these risks are even higher. The patients need their daily immunosuppressive medication also perioperatively [11,14], which may result in delayed wound healing and increased risk of postoperative infections [9]. In our series, these problems, however, were not observed.…”
Section: Discussionmentioning
confidence: 51%
“…It has been suggested that an anterior approach is contraindicated to avoid re-entering the previously operated pleural cavity in patients with heart transplant [9]. Coran et al [13] reviewed the results of spinal fusion in patients with congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Каждая нозологическая форма деформации имеет свои особенности клинических проявлений, динамики, течения -злокачественного или доб-рокачественного. При этом во всех этиологических группах сколиоза при тяжелой степени деформации возникают серьезные анатомические и функциональные изменения жиз-ненно важных органов и систем орга-низма [3,20,29,41,46]. Установлена закономерность сочетания врожден-ных аномалий позвоночника и дру-гих органов, заключающаяся в том, что сопутствующие пороки обычно локализуются в тех органах, кото-рые развиваются из сомитов, одно-временно дающих начало аномально развитым позвонкам.…”
unclassified